Application of Classroom Management in Improving Student Learning Discipline at MTs Tahfidzul Qur'an Braja Selebah - Yogi Gunawan Afandi; Mispani Mispani; Dian Anggraini (CV. Bimbingan Belajar Assyfa, 2026)
In today's era of digital disruption, mastery of financial literacy and Higher Order Thinking Skills (HOTS) is a crucial competency for students to face complex global economic challenges. The integration of religious values ​​into social science disciplines is seen as an effective, creative pedagogical strategy for building both character and analytical intelligence in students. This research is motivated by the lack of economics teaching materials in Madrasah Aliyah (MA) that can bridge modern economic theory with Islamic ethical foundations, as previous studies tended to separate the national curriculum and spiritual values. This study focuses on evaluating how integrated modules can impact the development of students' cognitive and affective aspects in understanding contemporary economic phenomena. The main objective of the research is to develop and test the feasibility and practicality of an economics module based on the integration of the Qur'an and Hadith at MA Sirojul Hikmah. Using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) Research and Development (R&D) model, this research involved validation by material and media experts, as well as a pilot test on 10th-grade students. The results showed that the module was deemed highly feasible by experts and received positive feedback from both teachers and students. Key findings identified that the use of sacred narratives as scaffolding in solving economic problems significantly increased learning enthusiasm and understanding of market ethics. The implications of this research confirm that reconstructing the economics syllabus through an integrative approach not only meets curriculum needs but also provides a pragmatic solution for developing students' moral resilience amidst the digital economy.